Left-handedness is associated with greater fighting success in humans - Richardson, T.; Gilman, R. T. (Scientific Reports, 2019)
Left-handedness is a costly, sexually dimorphic trait found at low frequencies in all human populations. How the handedness polymorphism is maintained is unclear. The fighting hypothesis argues that left-handed men have a negative frequency-dependent advantage in violent intrasexual competition giving them a selective advantage. In support of this, many studies have found that left-handed men are overrepresented among modern professional fighters, but studies typically find no difference in fighting success between left and right-handed fighters. We studied over 13,800 professional boxers and mixed martial artists of varying abilities in three of the largest samples to test this hypothesis to date, finding robust evidence that left-handed fighters have greater fighting success. This held for both male and female fighters, and for both percentage of fights won and an objective measure of fighting ability. We replicated previous results showing that left-handed fighters are strongly overrepresented in professional combat sports, but left-handed fighters did not show greater variance in fighting ability, a hypothesis suggested in previous studies. Overall we find strong evidence consistent with the fighting hypothesis.